Network Expansion from an Economic Perspective Using the Theory of Constraints, A Case Study at PT Telkom Indonesia - Khalid Ardhi Nurrahman (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study aims to describe the IndiHome network expansion process in the Blora region and analyze the key issues that arise using Bottleneck Analysis based on the Theory of Constraints. The research method used is descriptive qualitative with an intrinsic case study design. This approach was chosen because the researcher is part of the organization studied and therefore has a contextual understanding of operational processes and decision-making in the field. Through the application of analytical tools such as fishbone diagrams and TOC, this study identified key inhibiting factors, such as limited technical resources, inter-unit coordination, and complex administrative processes. The TOC provides strategic direction for overcoming these obstacles, focusing on high-value priority projects, utilizing automatic geotagging technology for data accuracy, increasing cross-unit collaboration to support implementation resources (SDI), and considering additional manpower or outsourcing to strengthen capacity. The results show that systematically managing these obstacles can accelerate network expansion and improve operational efficiency. Thus, the application of TOC has proven to be adaptive to the complex and dynamic telecommunications sector. Keywords: Theory of Constraints; bottleneck analysis; network expansion; telecommunications; PT Telkom Indonesia Abstrak Penelitian ini bertujuan untuk mendeskripsikan proses perluasan jaringan IndiHome di wilayah Blora dan menganalisis isu-isu kunci yang muncul menggunakan Analisis Bottleneck berdasarkan pendekatan Theory of Constraints (TOC). Metode penelitian yang digunakan adalah deskriptif kualitatif dengan desain studi kasus intrinsik. Pendekatan ini dipilih karena peneliti merupakan bagian dari organisasi yang diteliti sehingga memiliki pemahaman kontekstual tentang proses operasional dan pengambilan keputusan di lapangan. Melalui penerapan perangkat analisis seperti diagram tulang ikan dan TOC, penelitian ini mengidentifikasi faktor penghambat utama, seperti keterbatasan sumber daya teknis, koordinasi antar unit, dan proses administrasi yang kompleks. TOC berfokus pada proyek-proyek prioritas bernilai tinggi, menggunakan teknologi geotagging otomatis untuk akurasi data, meningkatkan kolaborasi lintas unit untuk mendukung sumber daya implementasi (SDI), dan mempertimbangkan penambahan tenaga kerja atau outsourcing untuk memperkuat kapasitas. Hasil penelitian menunjukkan bahwa pengelolaan hambatan tersebut secara berkala dapat mempercepat perluasan jaringan dan meningkatkan efisiensi operasional. Dengan demikian, penerapan TOC terbukti adaptif terhadap sektor telekomunikasi yang kompleks dan dinamis Kata Kunci: Teori Kendala; analisis hambatan; perluasan jaringan; telekomunikasi; PT Telkom Indonesia